2004
DOI: 10.1038/sj.bjc.6601948
|View full text |Cite
|
Sign up to set email alerts
|

Predicting aggressive outcome in T1N0M0 breast cancer

Abstract: Despite the excellent overall prognosis, unpredictable breast cancer recurrences and deaths also occur among T1N0M0 patients. We have evaluated clinically applicable methods for identifying aggressive outcome in T1N0M0 breast cancer. The material is based on aggressive T1N0M0 invasive ductal and lobular carcinomas diagnosed in Turku University Hospital and Jyväskylä Central Hospital, Finland, during 1987 -1997. We studied all the T1N0M0 breast cancers that had led to recurrency or death (n ¼ 21, 95% T1cN0M0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…Nevertheless, other markers such as PgR, ER␤2, Human Epidermal Growth Factor Receptor 2 (HER2), Epidermal Growth Factor Receptor (EGFR) and Ki-67 (a marker of proliferation) have also been shown to have prognostic and predictive relevance [14][15][16][17][18][19][20]. Defining the pattern of expression of these markers in ER␣+ breast cancer in elderly women and their predictive power relating to response to treatment could contribute significantly to the selection of an optimum therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other markers such as PgR, ER␤2, Human Epidermal Growth Factor Receptor 2 (HER2), Epidermal Growth Factor Receptor (EGFR) and Ki-67 (a marker of proliferation) have also been shown to have prognostic and predictive relevance [14][15][16][17][18][19][20]. Defining the pattern of expression of these markers in ER␣+ breast cancer in elderly women and their predictive power relating to response to treatment could contribute significantly to the selection of an optimum therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%
“…Securin and Ki-67 immunopositivities were determined by the fraction (%) of positively stained tumour cells and securin also by the intensity of staining (0, no staining; 1, weakly stained; 2, moderately stained; 3, strongly stained) at the areas of most pronounced staining, usually at the most cellular, infiltrating border of the tumour. Analysis of Ki-67 positivity was based on cutoff points at 10 and 20% of cancer cells (Ki-67o10%, 10%pKi-67p20% and Ki-67420%) adopted from clinical practice and based on research on breast cancer samples from Finland and other countries (Kronqvist et al, 2004;de Azambuja et al, 2007;Railo et al, 2007). The same cutoff points were applied for securin immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…2 This has been confirmed in the clinic: women with HER-2/neu positive breast cancer have a worse prognosis than those with HER-2/neu negative cancers; this is also true for T1N0M0 tumours. [3][4][5][6] Furthermore, HER-2/neu overexpression has been correlated with poor prognostic tumour characteristics such as higher histological grade, S phase fraction, increased tumour size, number of involved lymph nodes, lymphoid infiltration, p53 mutation, absence of bcl-2, absence of lobular histology, and negative or lower oestrogen receptor (ER) expression. [7][8][9][10][11][12][13][14][15] As a consequence, several, but not all, studies have confirmed that HER-2/neu overexpressing tumours show a lower response to tamoxifen in metastatic or early breast cancer.…”
mentioning
confidence: 99%